2017
DOI: 10.1152/jn.00194.2017
|View full text |Cite
|
Sign up to set email alerts
|

GABA transporters regulate tonic and synaptic GABAA receptor-mediated currents in the suprachiasmatic nucleus neurons

Abstract: GABA is a principal neurotransmitter in the hypothalamic suprachiasmatic nucleus (SCN) that contributes to intercellular communication between individual circadian oscillators within the SCN network and the stability and precision of the circadian rhythms. GABA transporters (GAT) regulate the extracellular GABA concentration and modulate GABA receptor (GABAR)-mediated currents. GABA transport inhibitors were applied to study how GABAR-mediated currents depend on the expression and function of GAT. Nipecotic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 70 publications
0
20
0
Order By: Relevance
“…The specific role of GABA neurotransmission in maintaining cellular synchrony remains controversial (see recent reviews by [2325]). GABA acts on synaptic GABA A receptors to mediate fast “phasic” signaling between SCN neurons, and extrasynaptic GABA A receptor activation provides SCN cells with a “tonic” GABA A current [26]. As a network, activity signaling by the tonic GABA-GABA A receptor current is a strong candidate to regulate the coupling strength between individual SCN neuronal oscillators [27,28].…”
Section: Cell To Cell Signalingmentioning
confidence: 99%
“…The specific role of GABA neurotransmission in maintaining cellular synchrony remains controversial (see recent reviews by [2325]). GABA acts on synaptic GABA A receptors to mediate fast “phasic” signaling between SCN neurons, and extrasynaptic GABA A receptor activation provides SCN cells with a “tonic” GABA A current [26]. As a network, activity signaling by the tonic GABA-GABA A receptor current is a strong candidate to regulate the coupling strength between individual SCN neuronal oscillators [27,28].…”
Section: Cell To Cell Signalingmentioning
confidence: 99%
“…Our model predicted that the astrocytic modulation of SCN neurons depended on mutual contributions from multiple intercellular signals (VIP: Marpegan et al, 2009; GABA: Barca-Mayo et al, 2017; Moldavan et al, 2017; and glutamate: Brancaccio et al, 2017; Scofield, 2018) regulated not only by neurons but also by astrocytes. Our signaling-blockade simulations suggested that the astrocytic binding of neuronally released VIP is an essential mechanism for establishing bidirectional communication between the 2 cell types.…”
Section: Discussionmentioning
confidence: 96%
“…We modeled calcium dynamics and internal calcium pools (i.e., IP3 and ryanodine stores; Mesiti et al, 2015; Vasalou and Henson, 2010) and included VPAC2 receptors (Masmoudi-Kouki et al, 2007) for binding VIP released by SCN neurons (Marpegan et al, 2009). The astrocyte model also included GABA transporters, which potentially regulate GABA concentrations in synaptic and extrasynaptic regions (Moldavan et al, 2015, 2017) as well as glutamate transporters for glutamate uptake and release (Brancaccio et al, 2017, 2019). The astrocyte was treated as a GABAergic and glutamatergic cell (Brancaccio et al, 2017; Schousboe et al, 2013; Yoon et al, 2012) that produced glutamate and stored GABA with circadian variations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…GAT-3 is the most abundant in astrocyte processes facing synapses and neuronal bodies (Boddum et al, 2016). GABA uptake via GAT-1 and GAT-3 activity influences GABAAR-mediated inhibitory transmission (Moldavan, Cravetchi, & Allen, 2017;Song et al, 2013); but additionally, GAT-3 activation stimulates the release of ATP/ adenosine from hippocampal astrocytes, which contributes to downregulate excitatory transmission via activation of presynaptic adenosine receptors (A1Rs) (Boddum et al, 2016), and enhances inhibitory transmission via activation of postsynaptic A1Rs (Matos et al, 2018). This downregulation of excitatory transmission via GABAergic activation contributes to the hippocampal heterosynaptic depression phenomena (Boddum et al, 2016;Serrano, Haddjeri, Lacaille, & Robitaille, 2006).…”
Section: Astrocytes Sense Gabaergic Signalingmentioning
confidence: 99%